5
May 22

Vector autoregression (VAR)

Vector autoregression (VAR)

Suppose we are observing two stocks and their respective returns are x_{t},y_{t}. To take into account their interdependence, we consider a vector autoregression

(1) \left\{\begin{array}{c}  x_{t}=a_{1}x_{t-1}+b_{1}y_{t-1}+u_{t} \\  y_{t}=a_{2}x_{t-1}+b_{2}y_{t-1}+v_{t}\end{array}\right.

Try to repeat for this system the analysis from Section 3.5 (Application to an AR(1) process) of the Guide by A. Patton and you will see that the difficulties are insurmountable. However, matrix algebra allows one to overcome them, with proper adjustment.

Problem

A) Write this system in a vector format

(2) Y_{t}=\Phi Y_{t-1}+U_{t}.

What should be Y_{t},\Phi ,U_{t} in this representation?

B) Assume that the error U_{t} in (1) satisfies

(3) E_{t-1}U_{t}=0,\ EU_{t}U_{t}^{T}=\Sigma ,~EU_{t}U_{s}^{T}=0 for t\neq  s with some symmetric matrix \Sigma =\left(\begin{array}{cc}\sigma _{11} & \sigma _{12} \\\sigma _{12} & \sigma _{22}  \end{array}\right) .

What does this assumption mean in terms of the components of U_{t} from (2)? What is \Sigma if the errors in (1) satisfy

(4) E_{t-1}u_{t}=E_{t-1}v_{t}=0,~Eu_{t}^{2}=Ev_{t}^{2}=\sigma ^{2}, Eu_{s}u_{t}=Ev_{s}v_{t}=0 for t\neq s, Eu_{s}v_{t}=0 for all s,t?

C) Suppose (1) is stationary. The stationarity condition is expressed in terms of eigenvalues of \Phi but we don't need it. However, we need its implication:

(5) \det \left( I-\Phi \right) \neq 0.

Find \mu =EY_{t}.

D) Find Cov(Y_{t-1},U_{t}).

E) Find \gamma _{0}\equiv V\left( Y_{t}\right) .

F) Find \gamma _{1}=Cov(Y_{t},Y_{t-1}).

G) Find \gamma _{2}.

Solution

A) It takes some practice to see that with the notation

Y_{t}=\left(\begin{array}{c}x_{t} \\y_{t}\end{array}\right) , \Phi =\left(\begin{array}{cc}  a_{1} & b_{1} \\a_{2} & b_{2}\end{array}\right) , U_{t}=\left(  \begin{array}{c}u_{t} \\v_{t}\end{array}\right)

the system (1) becomes (2).

B) The equations in (3) look like this:

E_{t-1}U_{t}=\left(\begin{array}{c}E_{t-1}u_{t} \\  E_{t-1}v_{t}\end{array}\right) =0, EU_{t}U_{t}^{T}=\left(  \begin{array}{cc}Eu_{t}^{2} & Eu_{t}v_{t} \\Eu_{t}v_{t} & Ev_{t}^{2}  \end{array}\right) =\left(\begin{array}{cc}  \sigma _{11} & \sigma _{12} \\  \sigma _{12} & \sigma _{22}\end{array}  \right) ,

EU_{t}U_{s}^{T}=\left(\begin{array}{cc}  Eu_{t}u_{s} & Eu_{t}v_{s} \\Ev_{t}u_{s} & Ev_{t}v_{s}  \end{array}\right) =0.

Equalities of matrices are understood element-wise, so we get a series of scalar equations E_{t-1}u_{t}=0,...,Ev_{t}v_{s}=0 for t\neq s.

Conversely, the scalar equations from (4) give

E_{t-1}U_{t}=0,\ EU_{t}U_{t}^{T}=\left(\begin{array}{cc}  \sigma ^{2} & 0 \\0 & \sigma ^{2}\end{array}  \right) ,~EU_{t}U_{s}^{T}=0 for t\neq s.

C) (2) implies EY_{t}=\Phi EY_{t-1}+EU_{t}=\Phi EY_{t-1} or by stationarity \mu =\Phi \mu or \left( I-\Phi \right) \mu =0. Hence (5) implies \mu =0.

D) From (2) we see that Y_{t-1} depends only on I_{t} (information set at time t). Therefore by the LIE

Cov(Y_{t-1},U_{t})=E\left( Y_{t-1}-EY_{t-1}\right) U_{t}^{T}=E\left[ \left(  Y_{t-1}-EY_{t-1}\right) E_{t-1}U_{t}^{T}\right] =0,

Cov\left( U_{t},Y_{t-1}\right) =\left[ Cov(Y_{t-1},U_{t})\right] ^{T}=0.

E) Using the previous post

\gamma _{0}\equiv V\left( \Phi Y_{t-1}+U_{t}\right) =\Phi V\left(  Y_{t-1}\right) \Phi ^{T}+Cov\left( U_{t},Y_{t-1}\right) \Phi ^{T}+\Phi  Cov(Y_{t-1},U_{t})+V\left( U_{t}\right)

=\Phi \gamma _{0}\Phi ^{T}+\Sigma

(by stationarity and (3)). Thus, \gamma _{0}-\Phi \gamma _{0}\Phi  ^{T}=\Sigma and \gamma _{0}=\sum_{s=0}^{\infty }\Phi ^{s}\Sigma\left( \Phi  ^{T}\right) ^{s} (see previous post).

F) Using the previous result we have

\gamma _{1}=Cov(Y_{t},Y_{t-1})=Cov(\Phi Y_{t-1}+U_{t},Y_{t-1})=\Phi  Cov(Y_{t-1},Y_{t-1})+Cov(U_{t},Y_{t-1})

=\Phi Cov(Y_{t-1},Y_{t-1})=\Phi \gamma _{0}=\Phi \sum_{s=0}^{\infty }\Phi  ^{s}\Sigma\left( \Phi ^{T}\right) ^{s}.

G) Similarly,

\gamma _{2}=Cov(Y_{t},Y_{t-2})=Cov(\Phi Y_{t-1}+U_{t},Y_{t-2})=\Phi  Cov(Y_{t-1},Y_{t-2})+Cov(U_{t},Y_{t-2})

=\Phi Cov(Y_{t-1},Y_{t-2})=\Phi \gamma _{1}=\Phi ^{2}\sum_{s=0}^{\infty  }\Phi ^{s}\Sigma\left( \Phi ^{T}\right) ^{s}.

Autocorrelations require a little more effort and I leave them out.